Marketing to the middle classmuslim : Kenali perubahannya, pahami perilakunya, petakan strateginya - YUSWOHADY (Gramedia Pustaka Utama, 2014)
The Six Principles of Marketing to the Middle Class Muslim. The Principle of Customer, The Pronciple of Positioning, The Principles of Differentiation, The Principle of Engagement, and The Principle of Value